Exploring organizational identity in strategy work: towards an embodied metaphor perspective - Jacobs, Claus D. (Henry Stewart Talks, 2012)
Organizational identity, Strategic management, Competitive advantage, Resource-based view, Strategy work, Identity work, Metaphors, Metaphorical reasoning, Embodiment, Embodied metaphors, Multi-modality, Multi-modal elicitation, Strategy as Practice